PENGARUH BUDAYA ORGANISASI DAN PENEMPATAN KERJA SERTA PENGAWASAN TERHADAP KINERJA PEGAWAI PDAM LEMATANG ENIM CABANG TANJUNG ENIM - Hertanudin, Hertanudin (Jurnal Ilmu Manajemen, 2015)
This research entitled the influence of Organizational Culture and Work Placement also Controlling on Employee Perfomance of PDAM Lematang Enim Tanjung Enim Branch. This Study aims to determine the effect Organizational Culture and Work Placement also Controlling on employee perfomance of PDAM Lematang Enim Tanjung Enim Branch. There are two problems in this study, firstly whether organizational culture and work placement also controlling have a significant together on employeeperfomance of PDAM Lematang Enim Tanjung Enim Branch. The second is organization culture and work placement also controlling have a significant effect partially on employee perfomance of PDAM Lematang Enim TanjungEnim Branch. The date used in this research is primer date with 60 respondens of General PDAM Lematang Enim Tanjung Enim Branch. Date test validity test and realibility test, with used multiple linear regression method and classic asumsion test are normality test, multicoliniarity test andheterocesdasticity with helpping program SPSS version 17.0 and the level significance 5%. Test result with SPSS linear regression shows the organization culture and work placement also controlling have a significant effect and together on employee performance of PDAM Lematang Enim Cabang Tanjung Enim. Partially, work placement and controlling have significant effect on employeeperfomance, and organization culture not have significant effect on employee perfomance. R value of 0,789 means that there is a strong link between organization culture (X1) and work placement (X2) and controlling (X3) of the employeeperfomance (Y). R square value 0,623 means that the ability of the independent variabel organization culture and work placement also controlling to explain to the employee perfomance variable (Y)